2022
DOI: 10.1038/s41467-022-28326-4
|View full text |Cite
|
Sign up to set email alerts
|

White matter myelination during early infancy is linked to spatial gradients and myelin content at birth

Abstract: Development of myelin, a fatty sheath that insulates nerve fibers, is critical for brain function. Myelination during infancy has been studied with histology, but postmortem data cannot evaluate the longitudinal trajectory of white matter development. Here, we obtained longitudinal diffusion MRI and quantitative MRI measures of longitudinal relaxation rate (R1) of white matter in 0, 3 and 6 months-old human infants, and developed an automated method to identify white matter bundles and quantify their propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 76 publications
4
57
0
Order By: Relevance
“…Myelinsensitive imaging is well posed to test these hypotheses, given the possibilities to examine myelin across the entire brain and to track individual developmental trajectories. In infants, Grotheer et al, (2022) showed that myelin levels at birth as well as spatial position contribute to age-related R1 changes in white matter bundles (Figure 4Ai). In certain tracts speed of myelination is inversely correlated to the pre-existing degree of myelin, whereas in other tracts it is associated with spatial axes (Figure 4Aii).…”
Section: Advancing Lifespan Research With Myelin-sensitive Imagingmentioning
confidence: 98%
See 3 more Smart Citations
“…Myelinsensitive imaging is well posed to test these hypotheses, given the possibilities to examine myelin across the entire brain and to track individual developmental trajectories. In infants, Grotheer et al, (2022) showed that myelin levels at birth as well as spatial position contribute to age-related R1 changes in white matter bundles (Figure 4Ai). In certain tracts speed of myelination is inversely correlated to the pre-existing degree of myelin, whereas in other tracts it is associated with spatial axes (Figure 4Aii).…”
Section: Advancing Lifespan Research With Myelin-sensitive Imagingmentioning
confidence: 98%
“…Notably, each dimension is sensitive to a different aspect of the myelin profile shape, related to myelin content at certain cortical depths [produced with data from (103)]. (133)]. ii.…”
Section: Figure 3: Relationship Of Local Myelin To Large-scale Cortic...mentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, it seems that white matter and cytoarchitecture are closely linked early in development, and that category-specific connections can emerge over development. Recent findings revealing that white matter fascicles can be reliably identified in individual newborns (Grotheer et al 2022) paving the way for future research to examine whether the relationship between cytoarchitecture and white matter connections is present at birth.…”
Section: Discussionmentioning
confidence: 99%